2014
DOI: 10.1111/ced.12341
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive cutaneous squamous cell carcinoma and psoriasis: response to cetuximab

Abstract: Cutaneous squamous cell carcinomas (CSCCs) comprise 20-30% of nonmelanoma skin cancers (NMSCs), and continue to increase in incidence. We report a case of a patient with severe psoriasis who had recurrent and eruptive CSCCs on her leg, which were successfully treated with cetuximab and radiotherapy. The patient had successful long-term clearance of her skin tumours, with the additional finding of resolution of psoriasis while on cetuximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Cetuximab has not been specifically developed in cSCC and no RCT has been conducted in this setting, but a number of individual case reports and some series, most often with a retrospective design, have been previously published to date in this indication (Table 4) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. The most relevant report is probably a multicenter phase II study of cetuximab in monotherapy for unresectable locally advanced or metastatic cSCC [27] that analyzed 31 finally assessable patients with ORR and DCR of 13 and 81%, respectively, in per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetuximab has not been specifically developed in cSCC and no RCT has been conducted in this setting, but a number of individual case reports and some series, most often with a retrospective design, have been previously published to date in this indication (Table 4) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. The most relevant report is probably a multicenter phase II study of cetuximab in monotherapy for unresectable locally advanced or metastatic cSCC [27] that analyzed 31 finally assessable patients with ORR and DCR of 13 and 81%, respectively, in per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, cetuximab, a chimeric human monoclonal antibody binding competitively and with high affinity to the EGFR, prevents receptor stimulation by endogenous ligands and inhibits proliferation, enhances apoptosis, and reduces angiogenesis, invasiveness, and metastatic spreading in target tissues. By analogy with advanced head and neck SCC where it proved efficient alone or associated with radiotherapy and/or chemotherapy [4,5,6,7], a number of case reports, small series reports [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], and scarce clinical trials or larger series [27,28,29] recently suggested that cetuximab may help control metastatic or locally advanced, unresectable cSCC, either alone or in combination with other therapies including systemic chemotherapy and/or radiotherapy. In order to add further information regarding its interest in advanced cSCC, the efficacy and safety of cetuximab alone or combined with chemotherapy in patients with locally advanced and metastatic cSCC treated at our institution were retrospectively analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these ligands are known to be overexpressed in psoriasis lesions . However, to date, no significant genetic signals for psoriasis have mapped to the EGFR or its ligands, and biological and pharmacological EGFRIs have by and large failed to improve psoriasis . Nevertheless, the striking inflammatory and hyperplastic skin phenotypes manifested by two strains of AREG TG mice , coupled with the marked overexpression of AREG and other EGFR ligands in psoriatic lesions, prompted us to further explore the biological outcomes following KC‐specific overexpression of hAREG in TG mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, AREG mRNA levels are much lower in normal and psoriatic lesional human skin in vivo than they are in cultured KC in vitro . While biological blockade of inflammatory signals including TNF, IL‐23 and IL‐17 markedly improves psoriasis , case reports of responses of psoriasis to EGFR inhibitors (EGFRIs) in patients with cancer have been sparse and have described both improvement and exacerbation . Moreover, antibodies and kinase inhibitors targeting the EGFR (EGFRIs) produce a papular and pustular eruption known as the PRIDE syndrome (papulopustules and/or paronychia, regulatory abnormalities of hair growth, itching and dryness due to EGFRIs) , which has proven to be the major side effect limiting the use of EGFRIs in cancer therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical improvement in psoriasis patients has been reported with cetuximab and tyrosine kinase inhibitors targeting EGFR, including erlotinib and lapatinib (Table ). In most cases, skin lesions improved promptly, showing full clearance after treatment.…”
mentioning
confidence: 99%